Voices of South Asian Women: Immigration and Mental Health - Ahmad, Farah; Shik, Angela; Vanza, Reena; Cheung, Angela M.; George, Usha; Stewart, Donna E. (Women & Health, 2005)
Purpose: This qualitative research aimed to elicit experiences and beliefs of recent South Asian immigrant women about their major health concerns after immigration. Methods: Four focus groups were conducted with 24 Hindi-speaking women who had lived less than five years in Canada. The audiotaped data were transcribed, translated, and analyzed by identification of themes and subcategories. Results: Mental health (MH) emerged as an overarching health concern with three major themes, i.e., appraisal of the mental burden (extent and general susceptibility), stress-inducing factors, and coping strategies. Many participants agreed that MH did not become a concern to them until after immigration. Women discussed their compromised MH using verbal and symptomatic expressions. The stress-inducing factors identified by participants included loss of social support, economic uncertainties, downward social mobility, mechanistic lifestyle, barriers in accessing health services, and climatic and food changes. Women's major coping strategies included increased efforts to socialize, use of preventative health practices and self-awareness. Conclusion: Although participant women discussed a number of ways to deal with post-immigration stressors, the women's perceived compromised mental health reflects the inadequacy of their coping strategies and the available resources. Despite access to healthcare providers, women failed to identify healthcare encounters as opportunities to seek help and discuss their mental health concerns. Health and social care programs need to actively address the compromised mental health perceived by the studied group.
Keywords: amériques; asie; asie du sud; canada; charge mentale; cours; discipline; femmes immigrantes; médecine; régions géographiques; santé; sciences; soc1061; stress post immigration; thématiques